Adaptive Inquiry-Based Learning Applications for Enhancing Students' Critical Thinking Skills: An Innovative Approach - Musdalifah Nihaya; Nurhilaliyah Nurhilaliyah; Harun Nihaya; Nurhidayat Nurhidayat (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Despite the urgency of fostering critical thinking in the Society 5.0 era, conventional digital learning often overlooks individual learner diversity, particularly in the post-pandemic educational landscape. This study addresses this gap by developing and validating a cloud-hosted learning application based on the Adaptive Inquiry Approach. Utilizing a Research and Development (R&D) methodology via the six-stage Luther-Sutopo model (concept, design, material collection, assembly, testing, and distribution), the platform dynamically tailored multi-modal content (text, audio, video, and simulations) to match diverse learning styles (visual, auditory, read/write, and kinesthetic) for elementary students (grades IV–VI). The findings indicated that validation by an interdisciplinary panel of experts established outstanding conceptual, pedagogical, and technical viability, with all composite evaluation scores exceeding the 80% threshold. Concurrently, empirical assessment instruments demonstrated optimal item difficulty and robust discriminatory power in tracing cognitive gains, while supplementary guidebooks achieved high institutional feasibility. By shifting from a static, uniform instructional delivery model to a dynamic, algorithmically tailored inquiry framework, this platform bridges the digital-pedagogical divide without diluting instructional substance. This study contributes to the educational technology literature by offering a powerful, scalable blueprint to systematically empower students' critical thinking skills in the post-pandemic era.